2009
DOI: 10.1111/j.1365-2966.2009.15338.x
|View full text |Cite
|
Sign up to set email alerts
|

The 6dF Galaxy Survey: final redshift release (DR3) and southern large-scale structures

Abstract: We report the final redshift release of the 6dF Galaxy Survey (6dFGS), a combined redshift and peculiar velocity survey over the southern sky (|b| > 10°). Its 136 304 spectra have yielded 110 256 new extragalactic redshifts and a new catalogue of 125 071 galaxies making near‐complete samples with (K, H, J, rF, bJ) ≤ (12.65, 12.95, 13.75, 15.60, 16.75). The median redshift of the survey is 0.053. Survey data, including images, spectra, photometry and redshifts, are available through an online data base. We desc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
588
6
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 923 publications
(622 citation statements)
references
References 75 publications
26
588
6
2
Order By: Relevance
“…Specifically we use the 6dFGS Data Release 3 (6dFGS DR3; Jones et al 2009), the final redshift release of the survey. As 2MRS, the 6dFGS is based mainly on the Ks-selected 2MASS, but is deeper, with a magnitude limit of Ks,tot = 12.65 mag, where Ks,tot is the total magnitude from the 2MASS.…”
Section: The 6dfgs Catalogmentioning
confidence: 99%
“…Specifically we use the 6dFGS Data Release 3 (6dFGS DR3; Jones et al 2009), the final redshift release of the survey. As 2MRS, the 6dFGS is based mainly on the Ks-selected 2MASS, but is deeper, with a magnitude limit of Ks,tot = 12.65 mag, where Ks,tot is the total magnitude from the 2MASS.…”
Section: The 6dfgs Catalogmentioning
confidence: 99%
“…There is a good quality optical spectrum available from the 6dF database (Jones et al 2009), here reported in Figure 5: surprisingly, it has a clear stellar appearance with well defined Balmer lines with the exception of the Hα, and it is classified as a DA white dwarf.…”
Section: The Cluster Mst 1945−2143 / 2fhlmentioning
confidence: 99%
“…Since publishing the previous release of the Stripe 82X catalog, we have mined these additional databases for spectroscopic redshifts: PRIMUS (Coil et al 2011), the Ross et al (2012) pre-BOSS pilot survey with Hectospec, 6dF (Jones et al 2004(Jones et al , 2009, and VVDS (Garilli et al 2008). We also have an ongoing ground-based follow-up campaign to target X-ray sources and have redshifts from WIYN HYDRA from observing runs in 2012 December, 2013 August-September, 2014 January, June, July, September, and 2015 January; from ISAAC on VLT from 2013 August; from NIRSPEC on Keck 2013 September; and from Palomar DoubleSpec from 2014 July and December.…”
Section: A3 Optical Spectroscopymentioning
confidence: 99%
“…We mined the following public spectroscopic catalogs to find redshifts, and where possible, optical classifications of the X-ray sources with SDSS counterparts: SDSS Data Release 12 (DR12; Alam et al 2015), 2SLAQ (Croom et al 2009), pre-BOSS pilot survey using Hectospec on MMT (Ross et al 2012), and 6dF (Jones et al 2004(Jones et al , 2009. We checked by eye the 41 spectra that had the zwarning flag set by the SDSS pipeline.…”
Section: Optical Spectramentioning
confidence: 99%
See 1 more Smart Citation